Role of diaxial versus diequatorial hydroxyl groups in the tumorigenic activity of a benzo[a]pyrene bay-region diol epoxide. - Chang, R L (1987)
Tumorigenic activities of the (7R,8S,9S,10R)-7,8-dihydroxy-9,10-epoxy-7,8,9,10-tetrahydro derivatives of benzo[a]pyrene [(+)-B[a]P diol epoxide-2] and 6-fluorobenzo[a]pyrene (6-FB[a]P diol epoxide-2) were evaluated in newborn CD-1 mice. A total dose of 14 nmol of either diol epoxide was administered to preweanling mice, and tumorigenic activity was determined when the mice were 32 to 36 weeks old. At the termination of the study, 13% of solvent-treated control mice had developed lung tumors with an average of 0.19 tumor per mouse. No other tumors were observed in control animals. (+)-B[a]P diol epoxide-2 induced pulmonary tumors in 60% of the mice with an average of 1.9 tumors per mouse, and 14% of the male mice developed hepatic tumors with an average of 0.18 tumor per mouse. In contrast, 6-FB[a]P diol epoxide-2 had no significant tumorigenic activity at the 14-nmol dose. Although both bay-region diol epoxides have the same absolute configuration, (7R,8S,9S,10R), the hydroxyl groups of (+)-B[a]P diol epoxide-2 prefer the pseudoequatorial conformation whereas the hydroxyl groups of 6-FB[a]P diol epoxide-2 prefer the pseudoaxial conformation. The tumorigenicity results reported here are the first direct demonstration that conformation of the hydroxyl groups in a bay-region diol epoxide, in addition to the documented effect of absolute configuration, is an important determinant in the tumorigenic activity of these ultimate carcinogens.